2021
DOI: 10.3390/rs13132588
|View full text |Cite
|
Sign up to set email alerts
|

Active-Learning Approaches for Landslide Mapping Using Support Vector Machines

Abstract: Ex post landslide mapping for emergency response and ex ante landslide susceptibility modelling for hazard mitigation are two important application scenarios that require the development of accurate, yet cost-effective spatial landslide models. However, the manual labelling of instances for training machine learning models is time-consuming given the data requirements of flexible data-driven algorithms and the small percentage of area covered by landslides. Active learning aims to reduce labelling costs by sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 66 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…ML methods are implemented using different algorithms applicable to LSMs, some of them widely used, such as random forest (RF) [28] or support vector machines (SVMs), [29] and others little explored, such as eXtreme Gradient Boosting (XGBoost) [18]. A frequently applied method is artificial neural networks (ANNs), with several studies performed in different countries [7,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML methods are implemented using different algorithms applicable to LSMs, some of them widely used, such as random forest (RF) [28] or support vector machines (SVMs), [29] and others little explored, such as eXtreme Gradient Boosting (XGBoost) [18]. A frequently applied method is artificial neural networks (ANNs), with several studies performed in different countries [7,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…According to information search in the DesInventar and EM-DAT (Emergency Events Database) databases, it was verified that during the period of 1970-2019, landslides in Ecuador caused 1642 deaths, 2456 houses destroyed, and there were losses exceeding USD 900 million [53]; 12 events were recorded during that period [54]. However, few studies were found that apply methodologies to determine landslide susceptibility in the country: Vorpahl et al [55] analyzed the contribution of statistical models to determine conditioning factors; Wang and Brenning [29] discussed an active-learning approach using SVM; and Soto et al [56] developed an approach to characterize landslides in an intramontane basin. All these studies were conducted in Loja province (southern Ecuador).…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of SVM is to search the optimal separating hyperplane that can maximize the interval between positive and negative samples in training dataset (Wang and Brenning 2021). Initially, SVM model was used as the supervised learning algorithm to solve binary classification problem, while the non-linear classification problem can be solved after introducing the kernel function.…”
Section: Support Vector Machine Model (Svm)mentioning
confidence: 99%
“…The SVM ensures that the extreme solution is the global optimal solution [15]. SVM has been proven to have many unique advantages in dealing with small samples, non-linear and high-dimensional pattern recognition, and is successfully applied in disaster prediction and assessment [15,18,19,27,[30][31][32].…”
Section: Support Vector Machine (Svm) Modelmentioning
confidence: 99%
“…As a result, more and more ML approaches have been optimized and applied for landslide susceptibility assessment in different regions. Examples are: Bayesian network (BN) [26,27], Naïve Bayes (NB) [19,27], artificial neural networks (ANN) [11,20,21,28,29], SVM [13,15,[18][19][20][21][22][23][24]27,[30][31][32], Logistic Regression (LR) [11,12,15,20,23,27,33,34], decision tree (DT) [19,22,30,[35][36][37], RF [22,31,[33][34][35][38][39][40][41], SVM-LR [23], convolutional neural network (CNN)-SVM, CNN-RF and CNN-LR [42]. These have all been used to quantitatively predict and assess the susceptibility for landslide in different regions of the world.…”
Section: Introductionmentioning
confidence: 99%